Pengaruh Pengetahuan, Kemudahan dan Risiko Terhadap Keputusan Penggunaan Quick Response Indonesian Standart (QRIS) - Zikriatul Ulya Zikri; Safwandi; Miftahul Jannah (Journal Research of Economic and Bussiness, 2023)
This study aims to determine the effect of knowledge of use, convenience and risk on the decision to use QRIS in Langsa City Supermarkets. This study uses quantitative research to determine the effect of knowledge, benefits and risks on the decision to use QRIS at the Langsa City supermarket. The population of this research is all people of Langsa City who shop and make payments using QRIS and it is not known how many. The sampling technique in this study used Accidental Sampling which is a sampling technique based on chance, that is, anyone who coincidentally meets the researcher can be used as a sample using the Wibisono formula, the number of samples in this study was 96 respondents. The results showed that the tcount of knowledge was 3.341 > from ttable of 1.661, with a significance value of 0.002 < alpha 0.05. The t-count value of the convenience is 2.462> from the t-table of 1.661, with a significance value of 0.018 <0.05, then Ha2 is accepted. The tcount value of risk is 4.922> from ttable of 1.661, with a significance value of 0.000 <0.05, then Ha3 is accepted. The results showed that simultaneously the variables of knowledge, convenience and risk had a positive and significant influence on the decision to use QRIS at the Langsa City Supermarket. This can be seen by the value of Fcount = 20,695> from Ftable 2.47 with a significance value of 0.000.